Legal Issues Raised by the Environmental Impacts of Photovoltaic Energy and Wind Energy Conservation Systems - Stoloff, Jonathan D.; Mallory, Karen L.; Stearns, Lisa R. (Columbia Journal of Environmental Law, 2020)